Ten years of battle with multiple recurrences of pediatric skull base chondrosarcoma: A case report - Mona Ariamanesh (Wiley, 2021)
Abstract In children and adolescents presenting with skull base sarcoma, treatment strategies will face challenging decisions due to the unique chemoresistant pathologies, limitations imposed by the not‐yet fully mature anatomical structures, and the small surgical site.